Real-Time Dosimetry in Endourology: Tracking Staff Radiation Risks - Susanne Deininger; Olaf Nairz; Anna Maria Dieplinger; Christian Deininger; Lukas Lusuardi; Christian Ramesmayer; Julia Peters; David Oswald; Maximilian Pallauf; Sophina Bauer; Mathias Christoph Brandt; Peter Törzsök (Diagnostics, 2024)
Background: To retrospectively investigate scatter radiation (SCR) exposure among staff in the endourology operating theatre. Methods: During surgeries under fluoroscopic guidance, five professional groups (urological surgeon [US], surgical nurse [SN], assistant surgical nurse [ASN], anaesthetist [A], and anaesthesia care [AC]) wore real-time dosimeters (Philips DoseAware System) on their head and chest over lead aprons between July 2023 and February 2024. The SCR data were analysed and correlated with procedural and patient factors. Results: In total, 249 procedures were performed, including 86 retrograde intrarenal surgeries and 10 percutaneous nephrolithotomies. Median SCR exposure was 38.81, 17.20, 7.71, 11.58, 0.63, 0.23, 0.12, and 0.15 Microsievert (µSv) for US chest (USC), US head (USH), SN chest (SNC), SN head (SNH), A chest (AC), AC chest (ACC), ASN chest (ASNC), and ASN head (ASNH), respectively. There was a significant correlation between DAP and SCR doses detected by USC, USH, SNC, SNH, AC, and ACC dosimeters (p < 0.05). The median chest-to-eye conversion factor (CECF) was 2.11 for the US and 0.71 for the SN. Conclusions: This study, using real-time dosimetry, is among the first to assess staff occupational SCR exposure in endourology. It highlights a substantial SCR exposure, indicating an occupational health hazard that warrants further investigation.